Attitudes towards physics. A study with high school students from the Colombian context (2021)
Science education should promote the development of competent students in science and develop their interest in science; however, although the role and relevance of science within society is evident; the interest towards it is not conscious, being the negative attitudes of the students the main problem in the teaching of physics, which translates into a deficient knowledge and lack of scientific vocation. This report aims to diagnose the attitudes of students in high school physics courses. The study was developed through a non-experimental, descriptive research design, obtained from the application of a Likert scale that evaluates attitudes towards physics, adapted and validated to the context of students in an educational institution in Colombia. The results indicate that the attitudes of the students are slightly favorable, which is an empirical precedent to continue with the studies on attitudes towards physic. This should be considered to enhance the learning processes in these students, especially for those who have their first approach to physical concepts and give importance to attitudes when teaching.